Isotope fractionation due to aqueous phase diffusion – What do diffusion models and experiments tell? – A review. (March 2019) - Wanner, Philipp; Hunkeler, Daniel
Abstract: For the interpretation of stable isotope ratio trends in saturated geochemical systems, the magnitude of aqueous phase diffusion-induced isotope fractionation needs to be known. This study reviews how five diffusion models (Fick, Maxwell-Stefan, Einstein, Langevin, Mode-Coupling Theory Analysis (MCTA) of diffusion) predict isotope fractionation due to aqueous phase diffusion and compares them with experimental results. The reviewed diffusion models were not consistent regarding the prediction of the mass (m) dependency of the aqueous phase diffusion coefficient (D). The predictions range from a square root power law (D ∝ m −0.5 ) to an opposite mass dependency of D (D ∝ m β ). Experimental studies exhibited consistently a weak power law mass dependency of the diffusion coefficient (D ∝ m −β with β < 0.5) for the vast majority of dissolved species and a larger diffusion-induced isotope effect for low weight noble gases (D ∝ m −0.5 ). The weak power law mass dependency of D for the species other than low weight noble gases is consistent with the MCTA of diffusion. The MCTA suggests that the weak power law mass dependency of D originates from interplays between strongly mass dependent short-term and mass independent long-term solute-solvent interactions. The larger isotope fractionation for low weight noble gases could be attributed to quantum isotope effects significantly magnifying the aqueous phase diffusion-induced isotope fractionation. Our review shows, that except for low weight noble gases a weak power law mass dependency of D is likely the most adequate assumption for aqueous phase diffusion-induced isotope fractionation in geochemical systems. Graphical abstract: Image 109987 Highlights: Review of how five diffusion models predict isotope fractionation. Compilation of experimental studies addressing diffusive isotope fractionation. Diffusion models are inconsistent in their prediction of isotope fractionation. Experimental data reveals a weak power law mass dependency of D for most solutes. Experimental data is consistent with Mode-Coupling Theory Analysis of diffusion.